Stagings of Sacrality in Istanbul’s Topkapı Neighbourhood - Haliloğlu, Nagihan (Kunsthistorisches Institut in Florenz - Max-Planck-Institut, 2013)
[No Abstract Available]
FSM Vakıf Üniversitesi, Medeniyetler İttifakı Enstitüsü